Sanksi Pidana Bagi Pemilik Apotek Terhadap Penjualan Obat Daftar G Secara Ilegal - Purwaningsih, Dewi; Widiastuti, Anggita Atika (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
The illegal sale of G-list drugs by pharmacy owners is a practice that violates the law and has the potential to endanger public health. This study aims to analyze the role of criminal witnesses and the challenges faced by law enforcers in prosecuting pharmacies selling illegal G-list drugs. The research method used is document analysis and interviews with related parties. The results of the study show that criminal witnesses play an important role in disclosing facts related to the illegal sale of List G drugs. Their testimony is vital evidence in the law enforcement process to bring perpetrators to justice. However, the process of providing testimony at trial faced several challenges, including threats to witness safety, intimidation, and harassment that could affect the integrity of testimony.